A rare case of congenital anomalies of hydrocephalus, cystic cephalus, microphthalmia and cleft lip on foetus – a case report - J, Arunpandian; C, Rama Selvam; Srivastava, Neeraj (Animal Reproduction Update, 2024)
A 6-year-old Holstein Friesian cross breed cattle was presented at Nettur veterinary dispensary in Tenkasi district. The cattle owner reported straining of the animal for 4 hours since morning, the serosanguinous mucoid discharge was noticed from the vulva. Vaginal examination revealed completely dilated cervix and presentation of the foetus head filled with fluid in-between both the hind limbs. To relieve the dystocia the foetus head was punctured with BP blade and the accumulated fluid was drained out followed by application of the obstetrical long eye hook on the eye and with snare on the forelimbs to expel out the fetus. The fluid therapy, antibiotic and anti-inflammatory was administered for five days